Relationship Between Staphylococcus aureus Biofilm Formation and Antibiotic Resistance that Isolated from Infections of the Urinary Tract in Babylon Province, Iraq - Salim Shamkhi Jaafar; Hasanain Khaleel Shareef (Medical Journal of Babylon)
Background: Hospital and community-acquired Staphylococcus aureus is a major concern for healthcare costs in addition to severe morbidity and mortality. Staphylococcus aureus biofilm generation contributes considerably to treatment failures. Objective: The current study intends to determine the association between biofilm formation and antibiotic resistance in isolated S. aureus. Materials and Methods: During the period from June 2022 to October 2022, 80 clean, voided, a midstream specimen of urine (MSU) were obtained from patients who attended the AL-Hashimiyah General Hospital. Cultured assays and conventional biochemical tests were performed to isolate and identify S. aureus and then confirmed by using VITEK2 system. Results: The results of the antimicrobial resistance test by the disc diffusion method for nine antibiotics from different groups showed Erythromycin 36 )66.66%(, Trimethoprim 31 )57.4%(, Amoxicillin-clavulanic acid 30 (55.55%), Ceftriaxone 23 (42.59%), Meropenem 17 (31.48), Ciprofloxacin 10 (18.51%), Nitrofuranate 10 (18.51%), Imipenem 5 (9.25%) while the less resistant showed with antibiotic Vancomycin 3 (5.55%). Through this study, it was found that women are more susceptible to urinary tract infection, where the ratio was (38/54) 70.37% compared to men (16/54) 29.62% susceptible to infection. Monitoring the resistance and spread of Staphylococcus aureus is of paramount importance in clinical management. The prevalence of biofilm producer isolated bacteria was 43 (79.6%) that 18 (41.8%) produced strong biofilm, 25 (58.1%) produced moderate biofilm, and 11 (20.3%) isolates produced non/weak biofilm. Conclusions: The study’s findings indicate that a high frequency of urinary tract infections is associated with Staphylococcus aureus also this pathogen highly biofilm-producing is developing resistance to numerous antibiotics used in this study and thus decreasing their value in the empirical management of simple UTIs. Therefore, it’s imperative to implement fresh approaches to combat antibiotic resistance. The high prevalence of S. aureus has been a serious health concern in urological patients.